STUDENTS' MATHEMATICAL REPRESENTATION ABILITY THROUGH IMPLEMENTATION OF MAPLE - Lusiana Lusiana; Yunika Lestaria Ningsih (IKIP Siliwangi and I-MES, 2018)
This research aims to investigate the students’ mathematical representation ability through the implementation of Maple in learning definite integral and those with ordinary learning. This research used a quasi-experimental design with a pretest-posttest control group design. The population of this study was students of 2nd semester of Mathematics Education Program at PGRI Palembang University Academic year 2017/2018. The sample in this study were students of class II.A and II.B, class II.A as a control group and class II.B as experiment group. Data were collected through a test of mathematical representation ability. Data in this study were analyzed through descriptive quantitative. The result of this study showed that students’ mathematical representation ability through implementation Maple in learning definite integral better than those who get the ordinary learning.